Surgery of the Thyroid and Parathyroid Glands - Oertli, Daniel; Udelsman, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The aim of this text is to create a unique in-depth comprehensive reference covering all surgically relevant thyroid and parathyroid diseases. It is a definite reference presenting the latest information on the management of common and rare disorders of the thyroid and parathyroid glands. International authorities provide detailed discussions on operative techniques and treatments that are accompanied by rationales for particular approaches advocated by the authors. The topics include the description of all surgically relevant pathologies, the preoperative surgical evaluation, decision making, and operative strategies for the different thyroid and parathyroid diseases. In addition, experts present the molecular basis for thyroid neoplasia and the current understanding of the genetics of inherited thyroid and parathyroid diseases. Evolving modern operative techniques like the minimally invasive videoscopic approach to the thyroid and parathyroids are also covered.
History of Thyroid and Parathyroid Surgery -- Embryology and Surgical Anatomy of the Thyroid and Parathyroid Glands -- Evaluation of Hyperthyroidism and Hyperthyroid Goiter -- Diagnostic Imaging of the Thyroid and Radioiodine Therapy -- Evaluation of Thyroid Nodules -- Fine-needle Aspiration Cytology of the Thyroid -- Technique of Thyroidectomy -- Surgery for the Solitary Thyroid Nodule -- Modified Radical Neck Dissection -- Thyroid Pathology -- Surgery for Medullary Thyroid Cancer -- Anaplastic Thyroid Carcinoma -- Thyroid Lymphoma and Other Metastatic Lesions -- Multinodular and Retrosternal Goiter -- Surgery for Hyperthyroidism -- Thyroiditis -- Complications in Thyroid and Parathyroid Surgery -- Outcomes Analysis in Thyroid Surgery: A Review of Patient and Provider Predictors -- Physiology and Pathophysiology of the Parathyroid Glands and Preoperative Evaluation -- Parathyroid Imaging -- Conventional Surgical Management of Primary Hyperparathyroidism -- Minimally Invasive Parathyroidectomy -- Endoscopic Parathyroidectomy -- Multiglandular Parathyroid Disease and MEN Syndromes -- Pathophysiology and Treatment of Secondary and Tertiary Hyperparathyroidism -- Parathyroid Carcinoma -- Reoperative Parathyroid Surgery -- Outcomes Analysis in Parathyroid Surgery.
Keywords: Medicine; Radiology; Interventional radiology; Endocrinology; Surgery; Medicine & Public Health; Surgery; Endocrinology; Diagnostic Radiology; Interventional Radiology; Electronic books